Homem também engravida? Participação do parceiro no pré-natal na atenção primária à saúde. - Vasconcelos, Ana Rebeca Araújo (2019)
This study aims to analyze the participation of partners in prenatal care in primary health care in the municipality of Quixeré, in the state of Ceará. Method: An intersectional survey was conducted with a population of 106 pregnant women and 31 partners in primary care prenatal care in the municipality of Quixeré, in July 2018, and interviewed between July and December of the same year, through data collection tools (developed by the researcher), with objective questions that covered sociodemographic aspects, access and quality of prenatal care and knowledge of pregnant women and partners about the prenatal partner, which were later typed in Google Forms ® and formatted in R® version 3 software.4.3, while the statistical analysis was conducted using IBM SPSS Statistics 22®. The correlation between the opinions of pregnant women and their respective partners was assessed using Cramer's V coefficient and Fisher's exact test, in which p < 0.05 is the decision rule to reject the absence of correlation in the opinion of both groups. Results: 68.9% of pregnant women and 61.3% of partners interviewed in the municipality of Quxeré considered themselves to be from rural areas, which explains the prevalence of agriculture over other occupations. The income of 65.5% of pregnant women and 48.4% of the partners was less than a minimum wage. The average age of the interviewees was 26 years for pregnant women and 30 years for the partners, who are, on average, 89.2% married or have a stable union,72.5% Catholic religion and 73.9% brown color. Regarding the partner's prenatal care, 90.3% of the men interviewed did not know the service. Regarding participation in prenatal care, 26% of the interviewed partners were not in consultations and of the 74% who participated, 68% had no exam performed or requested. 29% of the interviewed partners participated in collective activities during prenatal care. 85.3% of the partners who participated were effectively invited by their partners guided by the professionals, to the detriment of 57.9% of the participants whose pregnant women did not receive this guidance. The father's participation in prenatal care, childbirth and baby care was considered important by more than 90% of the pregnant women and partners interviewed. Conclusions: Half of the participants planned the pregnancy, the pregnant women had satisfactory care. The partners who participated in prenatal care had no access to tests and immunization. The participation of men in collective activities was small and the themes were considered relevant. The orientation of health professionals had a positive influence and the more pregnant women were stimulated, the more they invited the partners to participate.